Metachronous spinal cord involvement B cell and subcutaneous tissue involvement NK/T cell lymphoid proliferations and lymphomas arising in post-transplantation mimicking general NK/T cell lymphoma: a case report and review of the literature - Zhu, Yingxin; He, Lingbo; Zou, Heshan; Yao, Shuyan; Hu, Jinglin; Guo, Jing; Wang, Yini (Frontiers in Immunology, 2024)
Lymphoid proliferations and lymphomas arising in post-transplantation are potentially life-threatening complications after solid organ transplant (SOT) and hematopoietic stem cell transplant (HSCT). The lymphoid proliferations and lymphomas arising in post-transplantation originating from different cell lineages in the same patient are highly unusual. Herein, we delineate a case of isolated spinal cord involvement with B cell lymphoid proliferations and lymphomas arising in post-transplantation at 11 months post-transplantation, which was successfully treated with chemotherapy and intrathecal injection. Six months later, the patient again developed lymphoma arising in post-transplantation, presenting with predominant subcutaneous tissue involvement deriving from EBV-positive NK/T cells, and received four courses of chemotherapy. Ultimately, she achieved complete remission (CR). The report further contributes to our new insights into the unusual clinical presentations of lymphoid proliferations and lymphomas arising in post-transplantation.